Elastic properties of amorphous T0.75Y0.75B14 (T = Sc, Ti, V, Y, Zr, Nb) and the effect of O incorporation on bonding, density and elasticity (T′ = Ti, Zr). (12th January 2017) - Hunold, Oliver; Keuter, Philipp; Bliem, Pascal; Music, Denis; Wittmers, Friederike; Ravensburg, Anna L; Primetzhofer, Daniel; Schneider, Jochen M
Abstract: We have systematically studied the effect of transition metal valence electron concentration (VEC) of amorphous T 0.75 Y0.75 B14 (a- T 0.75 Y0.75 B14, T = Sc, Ti, V, Y, Zr, Nb) on the elastic properties, bonding, density and electronic structure using ab initio molecular dynamics. As the transition metal VEC is increased in both periods, the bulk modulus increases linearly with molar- and mass density. This trend can be understood by a concomitant decrease in cohesive energy. T ′ = Ti and Zr were selected to validate the predicted data experimentally. A-Ti0.74 Y0.80 B14 and a-Zr0.75 Y0.75 B14 thin films were synthesized by high power pulsed magnetron sputtering. Chemical composition analysis revealed the presence of up to 5 at.% impurities, with O being the largest fraction. The measured Young's modulus values for a-Ti0.74 Y0.80 B14 (301 ± 8 GPa) and a-Zr0.75 Y0.75 B14 (306 ± 9 GPa) are more than 20% smaller than the predicted ones. The influence of O incorporation on the elastic properties for these selected systems was theoretically studied, exemplarily in a-Ti0.75 Y0.75 B12.75 O1.25 . Based on ab initio data, we suggest that a-Ti0.75 Y0.75 B14 exhibits a very dense B network, which is partly severed in a-Ti0.75 Y0.75 B12.75 O1.25 . Upon O incorporation, the average coordination number of B and the molar density decrease by 9% and 8%, respectively. Based on these data the more than 20% reduced Young's modulus obtained experimentally for films containing impurities compared to the calculated Young's modulus for a-Ti0.75 Y0.75 B14 (without incorporated oxygen) can be rationalized. The presence of oxygen impurities disrupts the strong B network causing a concomitant decrease in molar density and Young's modulus. Very good agreement between the measured and calculated Young's modulus values is obtained if the presence of impurities is considered in the calculations. The implications of these findings are that prediction efforts regarding the elastic properties of amorphous borides containing oxygen impurities on the at.% level are flawed without taking the presence of impurities into account.